2012
DOI: 10.1002/jnr.23071
|View full text |Cite
|
Sign up to set email alerts
|

The expression of genes involved in glucose metabolism is affected by N‐methyl‐D‐aspartate receptor antagonism: A putative link between metabolism and an animal model of psychosis

Abstract: Psychosis has been associated with glucose metabolism impairment. Here, we explored the gene expression of hexokinase 1 (Hk1) and glucose transporter 3 (GLUT3) after the administration of a subanesthetic or a subconvulsant dose of ketamine in rats, considered to provide an animal model of psychosis. Indeed, Hk1 and GLUT3 are crucially involved in the glucose utilization in brain tissues and have also been implicated in the pathophysiology of psychosis. Quantitative brain imaging of transcripts was used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Such antidepressant effects of ketamine were subsequently inhibited by the additional treatment of an ERK1/2 inhibitor. Our results are consistent with previous findings by Lee et al 12 and Iasevoli et al 37 . Immunofluorescent staining further confirmed that astrocytes, but not neurons, exhibited enhanced expression levels of GLUT3 and P-ERK1/2 in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Such antidepressant effects of ketamine were subsequently inhibited by the additional treatment of an ERK1/2 inhibitor. Our results are consistent with previous findings by Lee et al 12 and Iasevoli et al 37 . Immunofluorescent staining further confirmed that astrocytes, but not neurons, exhibited enhanced expression levels of GLUT3 and P-ERK1/2 in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study are consistent with those of Tomioka et al in which they reported the effects of ketamine on glucose uptake by GLUT3 expressed in Xenopus oocytes 36 . In addition, Iasevoli et al found that ketamine increases GLUT3 mRNA expression in rats 37 . However, it is still unclear which signaling pathway may be associated with ketamine-induced increases in GLUT3 levels in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were sacrificed at 150 minutes after treatment, i.e. in a timerange that is consistent with previously published in situ hybridization studies on brain mRNA expression [19][20][21].…”
Section: Methodsmentioning
confidence: 96%
“…1). Procedures for probe labeling, in situ hybridization, and autoradiography were in agreement with previous published protocols [19,23].…”
Section: Methodsmentioning
confidence: 98%
“…One explanation for the mechanisms of prolonged analgesia exhibited by R5 is that it may induce key changes in early gene expression. It is known that ketamine and other NMDA receptor antagonists cause a variety of changes in expression of a significant number of genes [7, 8]. Therefore, we used mRNA sequencing to quantify gene expression changes induced in four key higher order pain-related regions of the rat brain by a 45 min infusion of ketamine and the related analogues.…”
Section: Introductionmentioning
confidence: 99%